Glycan Biosynthesis Ability of Gut Microbiota Increased in Primary Hypertension Patients Taking Antihypertension Medications and Potentially Promoted by Macrophage-Adenosine Monophosphate-Activated Protein Kinase - Zheng, Shuai; Piao, Chunmei; Liu, Yan; Liu, Xuxia; Liu, Tingting; Zhang, Xiaoping; Ren, Jingyuan; Liu, Yulei; Zhu, Baoli; Du, Jie (Frontiers in Microbiology, 2021)
Increasing evidences suggest that the gut microbiota have their contributions to the hypertension, but the metagenomic characteristics and potential regulating mechanisms in primary hypertension patients taking anti-hypertension drugs are not clear yet. We carried out metagenomic analysis in 30 primary hypertension patients taking anti-hypertension medications and 8 healthy adults without any medication. We found that bacterial strains from species, such as Bacteroides fragilis, Bacteroides vulgatus, Escherichia coli, Klebsiella pneumoniae, and Streptococcus vestibularis, were highly increased in patients, and these strains were reported to generate glycan, short-chain fatty acid (SCFA), trimethylamine (TMA), or be opportunistic pathogen. Meanwhile Dorea longicatena, Eubacterium hallii, Clostridium leptum, Faecalibacterium prausnitzii and some other strains were greatly decreased in patients’ group. The KEGG analysis found that, orthology groups and pathways related to glycan biosynthesis and multidrug resistance were significantly increased in patients’ group, and some of the hub genes related to N-glycan biosynthesis were increased in patients’ group, while those related to TMA precursor metabolism and amino acids metabolism showed both increase and decrease in patients’ group. Metabolites tested by untargeted LC-MS proved the decrease of acetic acid, choline, betaine, and several amino acids in patients’ fecal samples. Moreover, meta-analysis of recent studies found that almost all patients were taking at least one kind of drugs which were reported to regulate AMP-activated protein kinase (AMPK) pathway, so we further investigated if AMPK regulated the metagenomic changes by using angiotensin II induced mice hypertensive model on wild type and macrophage-specific AMPK-knockout mice. We found that the changes in Escherichia coli and Dorea and glycan biosynthesis related orthologs and pathways were similar in our cohort and hypertensive wild type mice, but reversed after AMPK knockout. These results suggest that the gut microbiota derived glycan, SCFA, TMA, and some other metabolites change in medications-taking primary hypertension patients, and medications might promote gut microbiota glycan biosynthesis through activating macrophage-AMPK.